Brand orientation in action – A transformational learning intervention - Gromark, Johan ; 0000-0002-3819-1047 (Journal of Business Research, 2020)
This article provides in-depth insight into the dynamics of a transformation from market orientation to brand orientation. By including a wide range of stakeholders in an action research intervention, a detailed description is provided regarding the transformation of a large Swedish public primary care organization during a turbulent marketization process. Brand management theory and practice are frequently based on uniformist and integrationist assumptions, which are questioned in this study. This is due to the fact that resistance and conflict are not only natural but necessary preconditions for transformational learning and thereby changing identities. The intervention shows how changing a strategic orientation is interwoven with identity dynamics on many levels. This study suggests that not only brand identities should be nurtured but also other social identities, such as local, professional and sector identities.
Keywords: Action research; Brand orientation; Multiple identities; Transformational learning